Income-related inequality in health insurance coverage: analysis of China Health and Nutrition Survey of 2006 and 2009 - Liu Jinan; Shi Lizheng; Meng Qingyue; Khan M (BMC, 2012)
Abstract Introduction China introduced the urban resident basic medical insurance (URBMI) in 2007 to cover children and urban unemployed adults, in addition to the new cooperative medical scheme (NCMS) for rural residents in 2003 and the basic health insurance scheme (BHIS) for urban employees in 1998. This study examined whether the overall income-related inequality in health insurance coverage improved during 2006 and 2009 in China. Methods The China Health and Nutrition Survey (CHNS) data of 2006 and 2009 were used to create the concentration curve and the concentration index. GEE logistic regression was used to model the health insurance coverage as dependent variable and household income per capita as independent variable, controlling for individuals' age, gender, marital status, educational attainment, employment status, year 2009 (Y2009), household size, retirement status, and geographic variations. The change in the income-related inequality in 2009 was estimated using the interaction term of income*Y2009. Results In 2006, 49.7% (4,712/9,476) respondents had health insurance: 13.4% with BHIS and 28.4% with NCMS. In 2009, 90.8% (8,964/9,863) had health insurance: 10.1% with URBMI, 18.3% with BHIS, and 57.6% with NCMS. The BHIS, URBMI, and NCMS programs had different patterns of population coverage over 10 income deciles. The concentration index was 0.15 in 2006 and 0.04 in 2009. The dominance test showed that the concentration curves were significantly different between 2006 and 2009 (p < 0.05). An income increase per capita by 10,000 RMB was associated with 25.5% more likely to have health insurance coverage (odds ratio = 1.255, 95% confidence interval: [1.130-1.393]). In 2009, there was significant improvement in the income-related inequality (p < 0.001). Discussions Comparing 2009 to 2006, the income inequality in health insurance coverage was largely corrected in China through rapid expansion of CHNS in rural areas and initiation of URBMI in urban areas.